2021
DOI: 10.1063/5.0040489
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tab parameters on the near-field mixing characteristics of a Mach 1.5 elliptic jet

Abstract: The effect of delta-tabs with its apex leaning downstream on the jet mixing characteristics of a Mach 1.5 elliptic jet of aspect ratio (AR) 3.37 is reported in this paper. The delta-tabs were placed along the minor and major axes of the elliptic nozzle, referred to as tab configuration C1 and C2, respectively. For each tab configuration, four different orientation angles varying from θ= 90∘ to 150∘ were studied, where θ= 90∘ is the tab positioned normal to the nozzle exit and θ= 150∘ is the tab oriented in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…There were four shock cells (C1, C2, C3 and C4) created in the supersonic jet core region for both the cases. The sink and rise of pressure portraits in Figure 3 show that across shock waves, the total pressure decreases, whereas through expansion waves it rises (Saif Akram et al , 2021). The extension of supersonic core length from the exit of nozzle was determined by the amount of fluctuations due to presence of shock waves in the jet core.…”
Section: Validation Of the Resultsmentioning
confidence: 99%
“…There were four shock cells (C1, C2, C3 and C4) created in the supersonic jet core region for both the cases. The sink and rise of pressure portraits in Figure 3 show that across shock waves, the total pressure decreases, whereas through expansion waves it rises (Saif Akram et al , 2021). The extension of supersonic core length from the exit of nozzle was determined by the amount of fluctuations due to presence of shock waves in the jet core.…”
Section: Validation Of the Resultsmentioning
confidence: 99%
“…It is worth mentioning that the tabs were also used to control noncircular jets like elliptic, rectangular, and square jets. [17][18][19][20][21][22][23][24] For elliptic jets, [17][18][19][20][21][22] it has been shown that the placement of tabs diametrically opposite to each other along minor axis is effective in mixing promotion than tabs along major axis. These studies show that the tabs are sensitive to nozzle geometry and tab-orientation at the exit of non-circular nozzle.…”
Section: Introductionmentioning
confidence: 99%